Aplicación de dos fuentes de abono orgánico en el cultivo de lechuga (Latuca sativa L.) - Guevara Cruz, Carlos Rommel (2011)
Among the vegetables grown in the area of business in recent times, lettuce appears to have a large local consumer demand. The research was conducted on the farm owned by Mr. Soraya Vanessa Inga Rubén Cobos located in Canton Pastaza Province Pastaza Puyo Parish, St. Martha sector range, right at 4.5 km from the main road via Napo Puyo Pastaza province , whose coordinates are: 18168127E, 9839452N. The work lasted 90 days and its main objective was to evaluate the agronomic performance with the application of two organic fertilizers in the cultivation of lettuce. (Latuca sativa L.) The factors under study were: Factor A = Fertilizers (guinea pig and sheep) and Factor B = dose (4 t ha-1, 7 t ha -1, 10 t ha -1). We used a total of 420 experimental units for this investigation. Design We used a Random Complete Block (RCB) with factorial two tickets and three doses plus a control with three replicates. We performed the analysis of variance (ADEVA) for the mean test was used Tukey test at 95% probability. The experimental measurements were: plant height (cm) Leaf length (cm), leaf width (cm) Root length (cm) foliage weight (g) and the corresponding economic analysis. The results: The highest point in lettuce plants were obtained with sheep manure in the dose of 4 t ha-1 in the three ages investigated. The long blade has the highest values with the guinea pig manure and sheep with a dose of 10 t ha-1. For leaf width sheep manure at a dose of 4 t ha-1 showed the best values. The root length obtained the highest value with the guinea pig manure in the dose of 10 t ha-1. The greater weight of cabbage lettuce was registered sheep manure in the dose of 4 t ha-1